PHARMACOKINETIC PROFILE OF SNEDDS PREPARATION EXTRACT OF PUTRI MALU LEAVES - Imran, Arlan; Nur’ainun Panigoro; Iksandi Aliwu; Melis Ma’ruf; Rajid Mbuinga (JURNAL KATALISATOR, 2024)
The Indonesian Ministry of Health reported that incidence of hepatitis in Indonesia has reached 20 million cases. As one of the preventive to reduce hepatitis disease, by consuming natural hepatoprotectors Putri malu plant. Therefore, Putri Malu needs to increase its bioavaibility in the body by making SNEDDS preparations. Purpose of this research is to knowing the formulation of variations in the concentration of oil, surfactant and cosurfactant in the preparation of SNEDDS Putri malu leaf extract on pharmacokinetics including Cpmax, Tmax and T1/2 values. Research method is a laboratory experimental by varying the concentration of VCO: Tween 80: PEG 400, namely F1 (1:6:3), F2 (1:7:2) and F3 (1:8:1). Results : formulation of the SNEDSS of Putri malu leaves has nanoemulsion times at F1-F3 each 3.65, 14.78 and 25.61 seconds. The Cpmax value of the third formula gets a value of 500 ppm, Tmax the three formulas get the same Tmax value of 0 hours and for the T1/2 value at F1-F3 each 4.222, 6836, and  2.826 hours. The best formula is found F2, this can be seen at T1/2, the longer the drug can last in the body, the less frequency of taking the drug.